Impact on the track from EMU commuter train - A. M. Brzhezovskiy (Вестник Научно-исследовательского института железнодорожного транспорта)
The largest part of operating fleet of EMU trains, operated on the railways of the JSC “Russian Railways”, belongs to the category “ЭП” - electric commuter trains for transporting passengers in suburban areas with a length of the turnover section not exceeding 200 km with a speed of up to 120 km/h. The category of “ЭП” electric trains is fully formed by the domestic rolling stock produced since 1993. After putting Safety Norms NB ZhT 03-98 into force in 1998 and subsequently entering Technical Regulations of the Customs Union - TR TS 001/2011 virtually all new or upgraded series of EMU trains of the category «ЭП» within the acceptance and certification tests were experimentally investigated by the Test Loop of the JSC “VNIIZhT” (ITs ZhT) for compliance with safety requirements from the conditions for ensuring normative level of indicators of interaction between rolling stock and the track. Main technical parameters were shown as well as design features of carriage part of EMU trains of the category “ЭП”. The following features were considered: comparative quantitative values and dependencies on the travel speed and the level of unbalanced accelerations of the experimental indicators of influence on the track of EMU train cars of the category “ЭП”, determined from the results of statistical processing of realizations of dynamic stresses in the throttle of rail sole and lateral forces; vertical and lateral (horizontal) forces transmitted from the wheels to the rail head; stability coefficients of assembled rails and sleepers from the transverse shift along the ballast, as well as the coefficients f of the transition from the axial stresses in the base of the rail to the stresses in the outer edge of the rail sole. The quantitative values of the impact indicators on the track of EMU train cars of the category “ЭП” with a design speed of 120 km/h, obtained from the results of complex certification and acceptance tests, are in the range of values regulated by the current regulatory documents. It is recommended to use the values of the impact indicators on the track to evaluate the design of the carriage part of EMU train cars at the design stage.